A new genus and species of Platypodini pinhole borers from South America (Coleoptera, Curculionidae, Platypodinae) - Kirkendall, Lawrence R. (Zootaxa, 2024)
I describe Amplioscapus new genus for Amplioscapus mirabilis new species represented by 164 specimens collected from tropical forests of the Amazon Basin and Guiana Shield. The new genus differs from all other Neotropical Platypodini genera in the antennae being inserted at the upper margin of the eyes in females; in the extraordinarily expanded antennal scape with dense long setae; in the numbers of transverse rugae on the protibiae; and in the numbers of small teeth on the anterior margin of the impression at the distal ends of the metanepisternum and metaventrite. The new pinhole borer genus is most similar to Megaplatypus Wood; in addition to the characters mentioned previously, the new genus differs from all known Megaplatypus in the pair of large mycangia on the female pronotum and the strongly alternating lengths of the elytral interstriae of males. Most individuals were taken from low elevations. Host records for specimens taken from cut trees show the new species to be a host generalist. The vast majority of specimens were captured by flight intercept traps, Malaise traps or canopy fogging, underlining the importance of passive trapping for tropical insect biodiversity surveys.